The Relationship of Perception and Foreign Language Learning Results - Sitaniapessy, Marcelina; Tuhumena, Wilhemina Ascaria; Maruanaya, Rita Fransina (Koli Journal : English Language Education, 2020)
German is the second obligatory foreign language that must be learnt by students at almost all high schools in Maluku Province. Learning German is not an easy task for Indonesian students due to the very different characteristics of the two languages. This results many students less interested in learning the language. Not a few of them find German language unpleasant and boring, so it is not surprising that many students get poor grades. If their perception is negative, then they surely are not motivated to learn it. Thus, these students need to be directed to know the benefits of learning German, so that they can foster their positive perceptions of the language and of course have a positive impact on their learning outcomes. This paper theoretically examined the relationship between perceptions of the benefits of learning German and student learning outcomes.